2012
DOI: 10.1111/j.1444-0938.2012.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of preschool vision screening referrals in South Auckland, New Zealand

Abstract: Background: Limited data are available on the causes of visual impairment in preschool children in New Zealand. We aimed to review demographic and visual parameters in children referred to the Ophthalmology Department, Manukau Super Clinic from vision screening programs in South Auckland. Methods: Retrospective medical record review of 131 children, aged three to five years, referred from community-based vision screening programs to the Ophthalmology Department for further assessment. Medical records were revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…The differences between the visual acuity values at 6-7 years and the screening values appear statistically significant, in line with what is reported in the literature [26][27][28][29][30][31][32], despite the difference in programs and procedures. There are no relevant associations…”
Section: Discussionsupporting
confidence: 89%
“…The differences between the visual acuity values at 6-7 years and the screening values appear statistically significant, in line with what is reported in the literature [26][27][28][29][30][31][32], despite the difference in programs and procedures. There are no relevant associations…”
Section: Discussionsupporting
confidence: 89%
“…The test has several disadvantages, including irregular progression size of the letters, the absence of a 6/7.5 (0.10 logMAR) line, truncation of the test at Snellen 6/6 acuity in the standard booklet, with measures of better visual acuity requiring the use of an additional booklet and a lack of contour interaction in the original uncrowded version . The Sheridan–Gardiner test has been used widely in vision screening programs; however, preschool vision screening programs that rely solely on measurements of visual acuity have low specificity and often produce high false positive referral rates compared to more comprehensive testing that is carried out by trained eye‐care providers . Sheridan suggests that normal monocular visual acuity in children aged five to seven is 6/4.5 (‐0.125 logMAR) on the single optotype version of the test and other authors have also reported better than 6/6 visual acuity obtained with Sheridan–Gardiner letters in young children.…”
Section: Measurement Of Recognition Acuity In Preschool Childrenmentioning
confidence: 99%
“…There remains a consequent risk of non‐visual acuity related conditions remaining undetected. A summary of a number of screening programs conducted in other countries is provided in Table …”
Section: Vision Screening Programs In Other Countriesmentioning
confidence: 99%